Estado nutricional, clima laboral y estilos de vida saludables en el personal asistencial del Hospital Iquitos “César Garayar García” – Loreto, 2023 - Huamán Pinedo, Angie Stephanie (2024)
The current study aimed to identify the nutritional status of the healthcare staff at the “Cesar Garayar Garcia” Hospital in Iquitos, 2023 year, and to examine the relationship with work environment and healthy lifestyle. This was a non experimental, quantitative, descriptive, correlational and cross-sectional study. The sample consisted of 260 health professionals, and instruments such as lifestyle questionnaires, work environment and nutritional evaluation sheet were used. In evaluating the healthcare personnel, it was observed that 21.2% had a normal BMI, 46.9% were overweight, 23.1% were classified as obese I, 6.5% are obese II, and 21.2% as obese III, across both genders. Additionally, abdominal circumference indicated that 55.8% were at very high risk, 26.9% at high risk, and 17.3% at low risk. Regarding the work environment, 53.5% of participants presented medium stress levels, 39.2% low stress, and 7.3% high stress. Furthermore, lifestyle assessments revealed that 80% of healthcare personnel in both genders exhibited unhealthy lifestyles, while only 20% maintained healthy lifestyles. The results indicate a statistically significant relationship between nutritional status, work environment, and lifestyle among the healthcare staff at the “Cesar Garayar Garcia” Hospital in Iquitos, 2023 year. Keywords: Nutritional status, body mass index, abdominal perimeter, work environment, lifestyles.